Re-Deeming the Past: Personal and Cultural Memory in Greek-Australian Poets - Nickas, Helen (Études helléniques / Hellenic Studies, 2005)
This article explores the theme of memory - personal and collective - in the work of three Greek-Australian poets: Dimitris Tsaloumas, Antigone Kefala and Yota Krili who migrated to the Antipodes in the fitties, wrote in English and made their mark within the wider Anglophone literature. These three writers are analyzed in terms of their imaginative dialogue with the past which they achieve by 'constructing' as opposed to simply reminiscing about, their past. The diaspora as a space of dislocation provides a vantage point out of which they can negotiate or untangle the complexities of a past, which is "a series of remembered and imagined pasts, each in a constant state of argument and flux: private pasts, family pasts, histories, cultural traditions. "All three writers in different ways are very conscious of memory as a tool which enables them to re-deem the past. The sense of loss in their writing is profoundly redemprive, and as already observed, "it is precisely in what is redeemed from time by memory" that their major strengths lie. ln the work of Tsaloumas, Kefala and Krili, we recognise that their 'otherness' as diasporic Greeks in Australia, offers them the opportunity ro see with (an)other eye, with the 'dual vision', attributed to the migrant.